Tradition and Community Spiritualism: Portrait of Islamic Socio-Religious in Kampung Kabare, North Waigeo, Raja Ampat - Sanjaya, Rama; Hailal, Fikri (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
This article, “Tradition and Community Spiritualism: Portrait of Islamic Socio-Religious in Kampung Kabare, North Waigeo, Raja Ampat,” departed from the tradition and spirituality that the Kabare camp ancestors passed down to the Kabare village community to preserve Islam amid the majority of the people who embraced the Nasrani religion. Prosperous Islam is guarded by the figure of people’s godly and is broad-minded about Islamic religious knowledge. In the Kabare camp, Islam is guarded, with knowledge as it is, and tries to be defended together. This phenomenon raises the question of how the portrait of the socio-religious survival of the Kabare people guards Islam amid the Christian community. This qualitative research uses the triangulation method approach and reference material, using The results of this study are that Islam is maintained and held because of the form of public awareness of Islamic history (historical consciousness) brought by the ancestors, namely the Tamima tribe, and awareness of preserving the traditions of Islam and spiritualism, manifested through the path of marriage and preserving existing traditions, such as burning incense with agarwood at the event of tahlilan.